Complex Medical Engineering - Wu, J.L; Ito, K.; Tobimatsu, S.; Nishida, T.; Fukuyama, H. (Springer Japan : Imprint: Springer, 2007)
In the twenty-first century, applications in medicine and engineering must acquire greater safety and flexibility if they are to yield better products at higher efficiency. To this end, complex science and technology must be integrated in medicine and engineering. Complex medical engineering (CME) is a new field that merges medical science and technology, and includes biomedical robotics and biomechatronics, complex virtual technology in medicine, information and communication technology in medicine, complex technology in rehabilitation, cognitive neuroscience and technology, and complex bioinformatics. Experts from academia, industry, and government research laboratories who have pioneered CME ideas and technologies describe its concept and research approach and discuss related hardware and software, science and technology, and medicine and engineering. This book will be invaluable to scientists, researchers, and graduates in the emerging field of CME.